The role of parental marital discord in the etiology of externalizing problems during childhood and adolescence. (20th December 2016) - Jarnecke, Amber M.; South, Susan C.; Elkins, Irene J.; Krueger, Robert F.; Tully, Erin C.; Iacono, William G.
Abstract: Previous research has established that parental marital discord is associated with higher levels of offspring externalizing behaviors, but it is unclear how parental relationship functioning is associated with the genetic and environmental variance on a factor of externalizing problems. Thus, the current study assessed how parental marital discord moderates genetic and environmental variance on offspring externalizing problems at two different ages: childhood and late adolescence. That is, the magnitude of genetic and environmental influences on offspring externalizing at ages 11 and 17 was examined as a function of parental marital discord. Consistent with a diathesis–stress model of psychopathology, it was hypothesized that with increasing marital discord, genetic influences on externalizing would be more pronounced. Rather, results indicated that for the 11-year-old sample, nonshared environmental influences were greater when parental marital discord was low, and comparatively, shared environmental influences contributed more to the variance in externalizing problems when parental marital discord was high. No moderation was found for the 17-year-old cohort. In contrast to studies that do not find an effect of the shared environment, these results provide evidence that the common rearing environment has an impact on externalizing problems in preadolescent children.